Le Mai 68 littéraire de François Maspero: L'éditeur comme relais intellectuel. - LEFORT-FAVREAU, JULIEN (Études Françaises, 2018)
While the importance of the publisher Éditions François Maspero in the political and intellectual fields is attested by numerous recent works, its contribution to the changes in the politics of literature surrounding May 68 merits particular attention. We hypothesize that François Maspero's activity leading up to and after 68 forms part of the literary field's politicization through the complex articulation between political theory and literary creation evident throughout his catalogue. Our focus here is four acceptations evident at Maspero, which represent different aspects of the conflictual place of literature in the social space of May 68. We first look at the prefaces written by Jean-Paul Sartre in two books published by Maspero: Aden Arabie by Paul Nizan and Les damnés de la terre (The Wretched of the Earth) by Frantz Fanon. We then analyze a series of articles by Georges Perec that appeared in the early 1960s in the journal Partisans. The third acceptation we observe turns up in publications devoted to Maspero's literary creations, notably poetry in translation. Finally, our analysis examines the "Théorie" series directed by Louis Althusser and its reflections on the tensions between art and ideology. An examination of these four literary variations shows that Maspero took a lead in giving voice to Third World issues, in fiercely criticizing the PCF aesthetic and in distancing from the principles of committed literature, thus presaging the major transformations of 68 continuing into the 1970s.